Efficient hydrogen production from glycerol photoreforming over Ag2OTiO2 synthesized by a sol–gel method. (6th July 2017) - Wang, Chao; Cai, Xiaoyan; Chen, Ying; Cheng, Zhengdong; Luo, Xianglong; Mo, Songping; Jia, Lisi; Shu, Riyang; Lin, Pengcheng; Yang, Zhi; Sun, Sifan; Pu, Enqi; et al.
Abstract: Photoreforming hydrogen production from glycerol aqueous solutions has been investigated over Ag2 OTiO2 catalysts with variable compositions (0.72–6.75 wt.% of Ag2 O) synthesized by a sol–gel method. The structural and morphologic characteristics were examined by means of X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), high resolution transmission electron microscopy (HRTEM) and Brunauer–Emmett–Teller (BET) method etc. By comparing the results of FESEM and DLS, aggregations of all samples were found to occur in both dry powder and water suspension states. The TiO2 based catalyst with 2.82 wt.% Ag2 O calcined under 500 °C showed less average particle size differences between in air and in aqueous state, suggesting better dispersion stability which could lead to a more efficient of using light. It was found that mixing certain amounts (0.72–2.82 wt.%) of Ag2 O to TiO2 could reduce anatase grain size and increased the specific surface area of the catalysts. The hydrogen production results indicated that the photocatalytic activity and the reaction rate of TiO2 were significantly improved by mixing Ag2 O. The optimal Ag2 O mixing amount and calcination temperature for H2 production was found. With an appropriate catalyst composition, the heterostructures could be well generated to enhance the separation of electrons and holes and it was also found that the desirable heterostructure was likely to disappear after the calcination temperature of 700 °C. Highlights: Ag2 OTiO2 catalysts with heterostructures were studied in photoreforming hydrogen production; Particle sizes in different phases were examined by FESEM and DLS for analyzing dispersion stability; Mixing certain amount of Ag2 O to TiO2 could reduce anatase grain size while increasing its BET value; The optimal catalyst composition and calcination temperature for H2 production was found.